A Promising Carbon/g‐C3N4 Composite Negative Electrode for a Long‐Life Sodium‐Ion Battery. Issue 39 (14th August 2019) - Weng, Guo‐Ming; Xie, Yu; Wang, Hang; Karpovich, Christopher; Lipton, Jason; Zhu, Junqing; Kong, Jaemin; Pfefferle, Lisa D.; Taylor, André D.
Abstract: 2D graphitic carbon nitride (g‐C3 N4 ) nanosheets are a promising negative electrode candidate for sodium‐ion batteries (NIBs) owing to its easy scalability, low cost, chemical stability, and potentially high rate capability. However, intrinsic g‐C3 N4 exhibits poor electronic conductivity, low reversible Na‐storage capacity, and insufficient cyclability. DFT calculations suggest that this could be due to a large Na + ion diffusion barrier in the innate g‐C3 N4 nanosheet. A facile one‐pot heating of a mixture of low‐cost urea and asphalt is strategically applied to yield stacked multilayer C/g‐C3 N4 composites with improved Na‐storage capacity (about 2 times higher than that of g‐C3 N4, up to 254 mAh g −1 ), rate capability, and cyclability. A C/g‐C3 N4 sodium‐ion full cell (in which sodium rhodizonate dibasic is used as the positive electrode) demonstrates high Coulombic efficiency (ca. 99.8 %) and a negligible capacity fading over 14 000 cycles at 1 A g −1 . Abstract : Flatland composites : Low‐cost carbon/graphitic carbon nitride (C/g‐C3 N4 ) composites can be used as the negative electrode for a long‐life sodium‐ion battery.